Grothendieck Property for the Symmetric Projective Tensor Product (Journal of Mathematical Study, 2021)
For a Banach space $E$, we give sufficient conditions for the Grothendieckproperty of $⨶_{n,s,π}E$, the symmetric projective tensor product of $E.$ Moreover, if $E^∗$ hasthe bounded compact approximation property, then these sufficient conditions are alsonecessary.
Keywords: Grothendieck property; homogeneous polynomial; projective tensor product.